CD44-mediated monocyte transmigration across Cryptococcus neoformans-infected brain microvascular endothelial cells is enhanced by HIV-1 gp41-I90 ectodomain. Issue 1 (December 2016) - He, Xiaolong; Shi, Xiaolu; Puthiyakunnon, Santhosh; Zhang, Like; Zeng, Qing; Li, Yan; Boddu, Swapna; Qiu, Jiawen; Lai, Zhihao; Ma, Chao; Xie, Yulong; Long, Min; et al.
Abstract Background Cryptococcus neoformans (Cn) is an important opportunistic pathogen in the immunocompromised people, including AIDS patients, which leads to fatal cryptococcal meningitis with high mortality rate. Previous researches have shown that HIV-1 gp41-I90 ectodomain can enhance Cn adhesion to and invasion of brain microvascular endothelial cell (BMEC), which constitutes the blood brain barrier (BBB). However, little is known about the role of HIV-1 gp41-I90 in the monocyte transmigration across Cn-infected BBB. In the present study, we provide evidence that HIV-1 gp41-I90 and Cn synergistically enhance monocytes transmigration across the BBB in vitro and in vivo. The underlying mechanisms for this phenomenon require further study. Methods In this study, the enhancing role of HIV-1 gp41-I90 in monocyte transmigration across Cn-infected BBB was demonstrated by performed transmigration assays in vitro and in vivo. Results Our results showed that the transmigration rate of monocytes are positively associated with Cn and/or HIV-1 gp41-I90, the co-exposure (HIV-1 gp41-I90 + Cn) group showed a higher THP-1 transmigration rate (P <  0.01). Using CD44 knock-down HBMEC or CD44 inhibitor Bikunin in the assay, the facilitation of transmigration rates of monocyte enhanced by HIV-1 gp41-I90 was significantly suppressed. Western blotting analysis and biotin/avidin enzyme-linked immunosorbent assays (BA-ELISAs) showed that Cn and HIV-1 gp41-I90 could increase the expression of CD44 and ICAM-1 on the HBMEC. Moreover, Cn and/or HIV-1 gp41-I90 could also induce CD44 redistribution to the membrane lipid rafts. By establishing the mouse cryptococcal meningitis model, we found that HIV-1 gp41-I90 and Cn could synergistically enhance the monocytes transmigration, increase the BBB permeability and injury in vivo. Conclusions Collectively, our findings suggested that HIV-1 gp41-I90 ectodomain can enhance the transmigration of THP-1 through Cn-infected BBB, which may be mediated by CD44. This novel study enlightens the future prospects to elaborate the inflammatory responses induced by HIV-1 gp41-I90 ectodomain and to effectively eliminate the opportunistic infections in AIDS patients.